Plasticity of protease gene expression in helicoverpa armigera upon exposure to multi-domain capsicum annuum protease inhibitor - Mahajan, Neha S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica et Biophysica Acta (BBA) - General Subjects, 2013)
Background A multi-domain Pin-II type protease inhibitor from Capsicum annuum (CanPI-7) is known to be effective against the insect pest, Helicoverpa armigera. The present study is an attempt to investigate the optimal dose of recombinant CanPI-7 (rCanPI-7) for effective antibiosis to H. armigera and further to characterize the responses of digestive proteases upon rCanPI-7 ingestion. Methods The gut protease activity was assessed biochemically and transcript accumulation pattern for selected trypsin and chymotrypsin genes was analyzed by quantitative Real-Time PCR. Results The growth retardation upon exposure to rCanPI-7 was more prominent in neonates as compared to third instar larvae. Influence of stage and dosage of rCanPI-7 was conspicuous on the expression and regulation of candidate trypsin and chymotrypsin genes in H. armigera. The transcript accumulation pattern correlated with the protease activity in rCanPI-7 exposed larvae. Conclusions We conclude that early exposure and specific dose of protease inhibitor are essential for effective antibiosis despite the large diversity and plasticity in the expression of protease genes in H. armigera. Moreover, it is also evident that the regulation and expression of H. armigera gut proteases are specific to the stage of PI exposure. General significance These results highlight the requirement of optimal PI concentration for effective growth retardation and for inhibiting the major gut proteases of H. armigera.